Digital solutions to transform agriculture: lessons and experiences in Ethiopia - Tamene, Lulseged D.; Abera, Wuletawu; Erkossa, Teklu (2020)
The Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT) – hereafter the Alliance and its various partners supported by GIZ-Ethiopia is supporting the transformation plan of Ethiopia through developing structured soils/agronomy database and promoting improved analytical approaches. Through organizing a coalition of experts (soil scientists, agronomists, geospatial analysis experts and data scientists), it was possible to materialize collation/collection of tenths of thousands of soil/agronomy datasets, developing standard data management portal, developing standard data collection guidelines and exploring various machine learning techniques to analyze dataset.